Critical Success Factors in Project Management: An Exploratory Study of an Energy Company in Brazil (Global Journal of Management and Business Research, 2014)
In a competitive business environment, the use of project management can allow organizations to strategically structure themselves to achieve their business goals and needs. In this way, organizations can invest in more effective project management that is aimed at achieving better performance, maximizing the possibility of success, and minimizing the chance of failure. Within this context, organizations must know which critical factors are most responsible for the success of a project to manage these factors in the best possible manner.The aim of this paper is to understand the relationship among critical success factors (CSF) in project management and the outcome of projects, from a contingency perspective. The field research developed in a company in the energy sector was done in two phases: document analysis and survey research with questionnaire applied to key stakeholders and 133 completed questionnaires were obtained. One result of the research indicates the CSF "Support from upper management" and "Scope clearly defined and detailed" as the most significant impact on the success of project management.
Keywords: project management project success project-critical success factors